Factors Determining the Quality of Life of Patients With COPD: A Review. Issue 6 (November 2017) - Mallouli, Manel; Dardouri, Maha; Ajmi, Thouraya; Mtiraoui, Ali; Ben Dhiab, Mohamed; Zedini, Chekib
Abstract : Predictors of health-related quality of life (HRQL) were controversial in the literature. To this end, we conducted a review to describe predictors of HRQL in patients with chronic obstructive pulmonary disease. The search comprised all the articles published until the end of 2016, which are consistent with our inclusion criteria. These factors could be structured into 5 groups: demographic factors, comorbidity, factors related to the disease, psychological factors, and other factors. The most common predictors of HRQL of chronic obstructive pulmonary disease patients were age, severity stage of the disease, dyspnea grade, and the number of exacerbations. Other determining factors include comorbidity, sex, body mass index, socioeconomic status, and educational level. This review of sparse and well-designed literature gives a current state-of-the-art that might be useful for future research.